2000
DOI: 10.1086/301168
|View full text |Cite|
|
Sign up to set email alerts
|

A Wide-Field 90 Centimeter VLA Image of the Galactic Center Region

Abstract: We present a wide-Ðeld, high dynamic range, high-resolution, long-wavelength (j \ 90 cm) VLA image of the Galactic center region. The image is centered on Sgr A, covers an area of 4¡ ] 5¡ with an angular resolution of 43A, and has a rms sensitivity of B5 mJy beam~1. The image was constructed from archival (1989 and 1991) VLA data of Pedlar et al. and Anantharamaiah et al. using new threedimensional image restoration techniques. These three-dimensional imaging techniques resolve the problem of non-coplanar base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
207
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(220 citation statements)
references
References 61 publications
11
207
2
Order By: Relevance
“…The magnetic field at the position of IRS 8 is considered to be parallel to the north-south axis (Aitken et al 1998;Morris 1998;LaRosa et al 2000;Glasse et al 2003). The presented polarization maps show polarization vectors parallel to the magnetic field of the NA as they would be produced by absorptive scattering on dust grains, aligned by Davis-Greenstein alignment (Davis & Greenstein 1951).…”
Section: Density Of the Bow Shockmentioning
confidence: 96%
“…The magnetic field at the position of IRS 8 is considered to be parallel to the north-south axis (Aitken et al 1998;Morris 1998;LaRosa et al 2000;Glasse et al 2003). The presented polarization maps show polarization vectors parallel to the magnetic field of the NA as they would be produced by absorptive scattering on dust grains, aligned by Davis-Greenstein alignment (Davis & Greenstein 1951).…”
Section: Density Of the Bow Shockmentioning
confidence: 96%
“…However, the manner in which the magnetic field in NRFs is amplified and how their electrons are accelerated is still debated (e.g., Heyvaerts et al 1988;Benford 1988;Serabyn & Morris 1994;Yusef-Zadeh 2003. Several observations have measured the radio and X-ray spectral indices of NRFs (e.g., Lang et al 1999b;LaRosa et al 2000;Lu et al 2003), but there has not been much systematic study. Thus, a goal of this survey work is to find new examples of NRFs and make more robust measurements of their spectral indices, to help better constrain theoretical models.…”
Section: Introductionmentioning
confidence: 99%
“…We have used recent advances in low-frequency and three-dimensional imaging to produce a wide-field image (%2=5) of the GC, with uniform and high resolution across the field, from 0.33 GHz VLA observations made between 1986and 1989(LaRosa et al 2000. A second image, designed to exploit the increase in number and quality of the 0.33 GHz receivers on the VLA since the acquisition of the data used by LaRosa et al (2000), is in progress and will be reported elsewhere (Nord et al 2002).…”
Section: Observationsmentioning
confidence: 99%
“…The observations that form our new GC imaging program were obtained in 1998. The data were calibrated in the standard fashion (similar to that of LaRosa et al 2000), with 3C 48 and 3C 286 used to calibrate the visibility amplitudes and frequent observations of the VLA calibrators B1822À096 and B1830À360 used to calibrate the visibility phases. The observations were made in spectral line mode in order to permit efficient excision of radio-frequency interference and to reduce bandwidth smearing effects during imaging, with Cygnus A used to calibrate the bandpass.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation